The Mediating Role of Destination Image on the Effect of Smart Tourism Applications on Behavioral Intentions of Tourists to Aceh: Moderated by Information Search - Ahmad Nizam; Sartiyah Sartiyah; Nurul Ilyana Muhd Adnan; Hendra Halim; Khairil Umuri; Teuku Muhammad Syahrizal (Sharia Economic and Management Business Journal (SEMBJ), 2026)
Background: This research examines the influence of Smart Tourism Applications on tourists' Behavioral Intentions in Aceh, with Destination Image as a mediating factor and Information Search Behavior as a moderating variable. Method: Using a quantitative approach, the research surveyed tourists who used smart tourism applications during their visit to Aceh. Results: The results reveal that the Smart Tourism Application significantly influences Destination Image, positively affecting tourists' intention to visit or revisit the destination. Furthermore, the destination image is a key mediator that links the Smart Tourism Application to tourists' behavioral intentions. However, Information Search Behavior did not significantly enhance the connection between the application and tourists' behavioral intentions. This indicates that the quality of information offered by the application plays a more critical role in influencing tourists' perceptions and building their confidence. The practical implication of this study is the need to optimize smart tourism applications to support Aceh's Syariah-based tourism by providing comprehensive information about local culture, halal facilities, and religiously guided tourism. Conclusion: This research contributes to the literature on technology in tourism, particularly in religious and cultural destination contexts, and offers insights for developing more effective destination marketing strategies.